Pengaruh Sistem Akuntansi Manajemen, Budaya Organisasi, dan Teknologi Informasi Terhadap Kinerja Manajerial : Studi Pada PT. Pegadaian Area Lampung - Yuni Rohaliza; Fajar Gustiawaty Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Nowadays, the business world is the world that is most often discussed in various forums, both national and international. The many discussions that are often discussed on this issue are the main benchmark for a country's progress. One measure of a country's progress is economic progress and the backbone of economic progress is the business world. The main problem that companies often face in any field cannot be separated from the funds needed, namely capital to finance the company's business, whether used for investment capital or working capital. A company that initially only cares about big profits will quickly do whatever it takes to achieve the desired target without thinking about the impact in the future. However, as time goes by, companies will also realize that every activity carried out must take into account future risks, which of course is the responsibility of the managerial side.